2002
DOI: 10.1111/j.1582-4934.2002.tb00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential arterial hypertension and polymorphism of angiotensiongen M235T gene

Abstract: Several candidate genes, chosen from the renin‐ angiotensin system, were examined for their association with essential hypertension. The genes of the renin‐ angiotensin system (RAS) are good candidates for such an approach because this system is well known to be involved in the control of blood pressure. One of these candidate genes is the gene encoding for angiotensinogen (the most important gene of the RAS associated with essential hypertension in the most population, is the gene for angiotensin‐converting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
(25 reference statements)
0
20
0
6
Order By: Relevance
“…Similarly, mutations in the angiotensinogen gene are associated with hypertension in humans (18,41,53). It has been suggested that angiotensinogen is not merely a passive substrate reservoir but also stabilizes plasma renin concentrations (by decreasing its metabolic clearance) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mutations in the angiotensinogen gene are associated with hypertension in humans (18,41,53). It has been suggested that angiotensinogen is not merely a passive substrate reservoir but also stabilizes plasma renin concentrations (by decreasing its metabolic clearance) (15).…”
Section: Discussionmentioning
confidence: 99%
“…PCR reactions and genotyping of -217G>A, -152G>A, -6G>A, T174M and M235T variants were done as described in detail elsewhere. 2,37,38,39 For -20A>C primers were designed (sense: 5' GCT TCT GGC ATC TGT CCT TC 3' and antisense: 5' CCG GCT TAC CTT CTG CTG TA 3') and genotyping was done by digesting 5 µl of the PCR product (protocol and conditions for PCR was similar to those used for the above mentioned polymorphisms except for the annealing temperature, which was 60°C for 50 sec) with 1.5 units of EcoO109 I restriction enzyme followed by electrophoresis using 3.5% agarose gel. The genotypes were identified based on the presence of bands representing allele A (AA -187 bp) or allele C (CC -124 bp and 63 bp) or both (AC -187 bp, 124 bp and 63 bp).…”
Section: Genotyping Of Polymorphismsmentioning
confidence: 99%
“…Ген AGT локализован на длинном плече 1-й хромосо-мы в локусе 1q42-q43, содержит 5 экзонов молекулярной массой 62-65 кДа [18]. В результате действия ренина от ангиотензиногена (АГТ) отщепляется концевой декапеп-тид, который и представляет собой ангиотензин I. Он пре-образуется в ангиотензин II (АТII) под действием ангио-тензинпревращающего фермента (АПФ).…”
Section: Discussionunclassified